2020
DOI: 10.1371/journal.pone.0232495
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an induced negative emotional state on autobiographical memory coherence

Abstract: Individuals who experience difficulty constructing coherent narratives about significant personal experiences generally report less psychological well-being and more depressive symptoms. It remains, however, unclear whether a negative emotional state, one of the core symptoms of depression, causes this impairment in autobiographical memory coherence. The current study aimed to examine the causal relation between mood and memory coherence by means of a mood induction paradigm. A group of 165 students were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This gain in working memory capacity was significantly related to the increase in memory coherence. Moreover, a recent study by Vanderveren, Aerts, Rousseaux, Bijttebier, and Hermans [39] showed that students who performed better on a working memory task were able to create more coherent narratives.…”
Section: Executive Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…This gain in working memory capacity was significantly related to the increase in memory coherence. Moreover, a recent study by Vanderveren, Aerts, Rousseaux, Bijttebier, and Hermans [39] showed that students who performed better on a working memory task were able to create more coherent narratives.…”
Section: Executive Functioningmentioning
confidence: 99%
“…In the prospective study by Vanderveren, Bijttebier, and Hermans [14] we cited to earlier, results seemed to suggest that students low in memory coherence were more vulnerable to the psychological impact of negative life events. Yet an experimental mood induction study demonstrated that inducing a negative mood (one of the core symptoms of depression) in women subsequently affects their ability to construct coherent narratives [39]. A large-scale longitudinal study in which the temporal relations between memory coherence and symptoms of psychopathology are investigated, could provide valuable insight into this matter.…”
Section: Plos Onementioning
confidence: 99%
“…One possibility is that a decline in mood at the start of the week and its improvement on the weekend (linked to work patterns) triggers concurrent searches for moodcongruent material; indeed, it is known that mental health problems are associated with cognitive biases toward threatening information (see Goodwin, Yiend, & Hirsch [2017] for a review pertaining to generalized anxiety disorder). A mood induction study would clarify this possibility, in which internet searches for climate change-related sites is compared for those induced to have either an anxious, dysphoric, or neutral mood (see Vanderveren et al, 2020, for a recent example of this procedure). The data do not allow for deciding between these two causal models at present, including the possibility of a bidirectional, reciprocal relationship between climate change concern and mental health concern.…”
Section: Discussionmentioning
confidence: 99%